EFL MATERIALS IN MADRASAH TSANAWIYAH: WHAT DO THEY REALLY NEED? - Zuliati Rohmah (TEFLIN, 2009)
Abstract: This study is a part of a larger research project, by a team of English Language Training for Islamic Schools (ELTIS), into the resources used in MTs. This paper talks about the needs of Islamic Junior High Schools (Madrasah Tsanawiyah, henceforth, MTs) for ELT materials. The research involved a number of principals, teachers and students of MTs in two areas: East Java and West Nusa Tenggara. Presentation and discussion of the analysis of the needs will be followed with some suggestions addressing some major weaknesses in the resources currently available in MTs.